SUMBER DAYA INÉWAI LIYAN MANGGARAI DALAM PERSPEKTIF LIFEWORLD - Barung, Kanisius (STKIP Santu Paulus Ruteng, 2015)
Abstract: Manggarain Inéwai Liyan Resource in the Lifeworld Perspective. Inéwai in this essay is the Manggarain women in West Flores, Nusa Tenggara Timur. Liyan is a barrier that explains the phenomenon of womens’ resources that are still locked in the socio-cultural reality. The writing of the inéwai liyan problem is to explain the values of the inéwai presence (being) in the lifeworld perspective from time to time. Data collected in this writing is from the sources (printed documents, knowledge of the author, and sources) using the observation and interview methods. Data is explained using a unified method.From the perspective of lifeworld it is revealed that the value of the Manggarain inéwai existence is represented in the figure of liyan. The value of the Manggarain inéwai is described as helpless, illiterate, cannot compete, passively waiting for the proposal, victims of violence, whose love was mortgaged on behalf of the indigenous , and a minor role (subordinate, husband’s servant, housewife). Liyan actually has the power of beauty and hospitality, as well as skills in life, but liyan shackled in socio-cultural reality of the past. Liyan must learn to manage self values to be independent or empowered to be free from the powerlessness and becomes reliyan, as the great women figures of the future. Keywords: resource, women, values, lifeworld Abstrak: Sumber Daya Inéwai Liyan Manggarai dalam Perspektif Lifeworld. Inéwai dalam esai ini adalah perempuan Manggarai di Flores Barat, Nusa Tenggara Timur. Liyan adalah pembatas yang menjelaskan fenomena sumber daya inéwai yang masih terbelenggu dalam realitas sosiokultural. Masalah inéwai liyan ditulis untuk mengeksplanasi nilai-nilai keberadaan inéwai dalam perspektif lifeworld dari waktu ke waktu. Data tulisan ini dikumpulkan dari sumbernya (dokumen cetak, pengetahuan penulis, dan narasumber) dengan menggunakan metode pengamatan dan wawancara. Data dieksplanasi dengan metode padan. Dari perspektif lifeworld itu terungkap nilai keberadaan inéwai Manggarai yang direpresentasikan dalam sosok liyan. Nilai keberadaan inéwai Manggarai diterangkan sebagai liyan yang tidak berdaya, yang buta aksara, yang kalah bersaing, yang pasif menunggu pinangan, yang menjadi korban kekerasan, yang cintanya tergadaikan atas nama adat, yang berperan minor (bawahan, hamba suami, ibu rumah tangga). Sebenarnya liyan memiliki daya kecantikan dan keramahan serta kecakapan hidup, tetapi liyan terbelenggu dalam realitas sosiokultural pada waktu lampau. Liyan harus belajar mengelola nilai diri untuk berdaya secara mandiri atau diberdayakan supaya bebas dari ketidakberdayaan menjadi reliyan sebagai sosok perempuan hebat masa depan. Kata kunci: sumber daya, perempuan, nilai, lifeworld